Nietzsche and His “Ethics of Friendship”:With and Against Tradition [Nietzsche y Su “Ética de la Amistad”: Con y Contra la Tradición1] - Aurenque-Stephan, D (Universidad de Talca, 2018)
Although friendship represents one of the most typically human phenomena, it has not had a leading place in the list of the main questions and themes of philosophy. Nevertheless, friendship has been an issue that even if marginal, has indeed a tradition in philosophy. Precisely Nietzsche’s conception of friendship is located in and against that tradition. In this contribution I do not intend to offer a comprehensive view of Nietzsche’s “ethics of friendship”, but rather to systematically characterize some of its central approaches. I will focus on the fundamental aspects of the Nietzschean understanding of friendship, contextualizing that understanding in the general framework of the philosopher’s thinking. For that purpose, I will explain four aspects in which, in my opinion, we can explain Nietzsche’s thinking on friendship: a) Friendship as ethical praxis; b) the relationship between love, marriage and friendship; c) the rehabilitation of the enemy, and d) friendship as political praxis. Finally, I will offer some conclusions that may allow us to recognize in Nietzsche a philosopher who always thinks with and against the tradition. © 2018 Universidad de Talca. All Rights Reserved.